2007
DOI: 10.2337/dc06-1769
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Glycemic Control in Type 2 Diabetes During Acute- and Maintenance-Phase Treatment of Major Depressive Disorder With Bupropion

Abstract: OBJECTIVE -Depression management in both short-and longer-term treatment studies has been associated with improvement in glycemic control. We used bupropion hydrochloride (Wellbutrin XL) to determine whether this improvement could be attributed to changes in anthropometrics or diabetes self-care.RESEARCH DESIGN AND METHODS -Ninety-three patients with type 2 diabetes and major depressive disorder (MDD) received bupropion hydrochloride in a two-phase, openlabel treatment trial. Those who completed the acute phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 52 publications
6
74
0
3
Order By: Relevance
“…Healthy Border 2010 identifies diabetes and mental health issues as border health priorities. Screening diabetics for depression is of great importance because there is evidence that treatment of depression improves glycemic control 64 and increases a patient's quality of life. 65 Healthy Border 2010, however, recognizes that access to mental health services along the US Mexico border is problematic because of a shortage of specialty mental health providers and services.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy Border 2010 identifies diabetes and mental health issues as border health priorities. Screening diabetics for depression is of great importance because there is evidence that treatment of depression improves glycemic control 64 and increases a patient's quality of life. 65 Healthy Border 2010, however, recognizes that access to mental health services along the US Mexico border is problematic because of a shortage of specialty mental health providers and services.…”
Section: Discussionmentioning
confidence: 99%
“…Novel approaches to investigating the role of subclinical symptoms of depression in patients with type 2 diabetes may also be valuable. As of yet, it is unclear whether interventions that reduce symptoms of depression could improve diabetes self-care, but there is recent evidence supporting this possibility (26). Efforts to reduce barriers to effective diabetes management should include both increased screening for depression in the primary care setting and increased recognition that even subclinical symptoms of depression may negatively impact diabetes self-care behaviors.…”
Section: Self-care Among Patients Not Meeting Criteria For Major Deprmentioning
confidence: 99%
“…However, one study used a longitudinal design and found significant relationships between depressive symptoms at baseline and increases in symptoms of depression over time and a variety of self-care behaviors assessed 9 months later, even when baseline levels of self-care were controlled (14). Another study of an open-label treatment trial of bupropion hydrochloride in patients with type 2 diabetes and major depressive disorder found that depression severity, BMI, total fat mass, and A1C decreased during the acute phase of treatment, whereas adherence to diet and exercise improved significantly (30). The pattern of findings from these studies is consistent with a causal relationship but does not provide conclusive proof.…”
Section: Moderation Analysesmentioning
confidence: 99%